Changes in the production factor?s structures in agriculture in the light of price adjustments. A case study of selected EU countries = Zmiany struktur czynników wytwórczych w rolnictwie w świetle uwarunkowań cenowych. Studium przypadku wybranych krajów UE - Czyżewski, Andrzej; Staniszewski, Jakub (Zielona Góra: Faculty of Economics and Management Press)
The conducted research concerns the issue of the impact of the prices on the volume and the productivity of labour and capital factors. The purpose of the article is to compare to what extend changes in the structures of agricultural production factors in the agriculture of selected EU countries (Poland, Hungary, Italy) in years 1999-2013 are the consequence of adaptation to price conditions on the agricultural products markets and production factors markets.
Keywords: elastyczność cenowa; struktura produkcji; czynniki wytwórcze; rolnictwo; UE; price elasticity; structure of production; factors of production; agriculture; EU